Pengaruh Pemakaian Biofilter Dengan Media Tempurung Kelapa Sawit Tephadap Penurunan Polutan Organik Di Dalam Air Limbah Industri Tahu Dan Tempe - Budijono '; M. Hasbi (Universitas Riau, 2010)
The objective of this study is to assess the influence of palm shell biofilter aplication in degrading organic pollutant in fermented soybean cake waste industryat aerobic system. This study was carried out in fermented soybean cake industry atTampan region, Pekanbaru. The total amount of wastewater that produced from onesmall industry fermented soybean cake is around 2 m3/day, and now is collected inwastewater drainage. Wastewater treatment of aerobic system. Basically thiswastewater treatment relies on bacteria in degrading pollutants. The use of palmshell is to increase specific surface of media for attaching bacteria. The systemconsist of one reactor that is made of 5 mm glass, and the volume reactor 140 liter.The reactor was equipped with one circulating pump and blower in the aerobic zone.It took 30 days for seeding micoorganism. The reactor were run in four differentresident time, namely 4 hours, 3 hours, 2 hours and 1 hour. The raw water used inthis experiment is waste water from tofu and fermented soybean cake industries thathave organic compound around 594.08 – 1276.64 mg/l. The water for physical andchemical analysis is sampled daily. It took from raw water and aerobic colum ofreactor. The results from 192 physical and chemical parameters from 24 watersamples showed that the palm shell biofilter gives a little influence to degradeorganic pollutant. The efficiency process in decreasing organic compund valuearound 6.47 – 16.48%, TSS 32.47 – 97.19%, TDS 7.89 – 19.25%, ammonia 0.66 –2.75%, total phosphate 1.76 – 5.13%, and nitrate 3.24 – 6.99%. The shorter retentiontime, the less removal efficiency of organic matter, TSS, TDS, ammonia, totalphosphate and nitrate.Key words : Biofilter, Biofilm, Wastewater Treatment, Aerobic Reactor, Organic Waste, Waste of Tofu and Fermented Soybean Cake Industry.